Algorithms and Computation 21st International Symposium, ISAAC 2010, Jeju, Korea, December 15-17, 2010, Proceedings, Part II - Cheong, Otfried.; Chwa, Kyung-Yong.; Park, Kunsoo. (Lecture Notes in Computer Science, 2010)
This book constitutes the refereed proceedings of the 21st International Symposium on Algorithms and Computation, ISAAC 2010, held in Jeju, South Korea in December 2010. The 77 revised full papers presented were carefully reviewed and selected from 182 submissions for inclusion in the book. This volume contains topics such as approximation algorithm; complexity; data structure and algorithm; combinatorial optimization; graph algorithm; computational geometry; graph coloring; fixed parameter tractability; optimization; online algorithm; and scheduling.